Pharmacoepidemiological Analysis of Antibacterial Agents Used in a Provisional Hospital in Aktobe, Kazakhstan, in the Context of COVID-19: A Comparison with the Pre-Pandemic Period - Aigerim A. Balapasheva; Gaziza A. Smagulova; Aigul Z. Mussina; Liliya E. Ziganshina; Zhansulu Zh. Nurgaliyeva (Antibiotics, 2023)
In the context of the global spread of Coronavirus Disease 2019 (COVID-19), the issue of evaluating and optimizing the use of antibacterial drugs becomes especially relevant. The coronavirus pandemic has provided a unique opportunity to study the dynamics of the consumption of antibacterial agents and their impact on public health. The rational use of antibiotics is a key aspect of the fight against antimicrobial resistance, which makes this study particularly important. The aim of this study was to assess changes in the consumption of antibacterial drugs among patients hospitalized with COVID-19 during the peak of the 2020 pandemic and compare them with data from 2019 prior to the pandemic. This study collated data on antibacterial drug consumption in a regional hospital in Aktobe, which served a large population of patients during the pandemic. A pharmacoepidemiological study was conducted using the Anatomical Therapeutic Chemical (ATC)/Defined Daily Dose (DDD) methodology. The pharmacoepidemiological study using the international ATC/DDD methodology revealed a concerning pattern of irrational consumption of antibacterial drugs, including cephalosporins, azalides, second-generation fluoroquinolones, and systemic aminoglycosides in Aktobe. Among antibacterial drugs during the pandemic, the most significant increase in consumption was from the group of cephalosporins (19,043 DDD/100 bed-days). The share of their consumption was 35.4% of the total consumption of antibacterial drugs. Pharmacoepidemiological studies using the international methodology ATC/DDD showed an alarming picture of irrational consumption of antibacterial drugs of the group of cephalosporins, azalides, fluoroquinolones, and aminoglycosides in Aktobe, and, in this case, excessive use of the identified antibiotics raises concerns about the possibility of increasing the problem of resistance to microbes.